Surgical treatment of bullous lung disease. Issue 12 (December 1981) - Potgieter, P D; Benatar, S R; Hewitson, R P; Ferguson, A D
Abstract : Clear guidelines for the selection of patients with large pulmonary bullae and severely impaired lung function for surgery remain to be defined. Twenty-one such patients operated on between 1971 and 1977 are reviewed in an attempt to shed some light on this difficult problem. Four of six patients with preoperative hypercapnia survived and were improved by surgery. There was no mortality among the remaining 15 patients of whom 14 were improved symptomatically by surgery (with improvement in FEV1 and vital capacity in 9). Preoperative bronchograms were used to help identify patients suitable for surgery. The presence of bronchiectasis was predictive of postoperative complications. Better results were obtained in those patients in whom plication of bullectomy could be performed than in those requiring lobectomy.